Facility E-complaint (E-aduan fasiliti) / Mohamad Farid Mansor - Mansor, Mohamad Farid (2016)
Universiti Teknologi MARA campus Pulau Pinang start operations at June 16, 1996 at a temporary campus in Permatang Pasir and it was the 11th UiTM campus. Pulau Pinang real UiTM campus is in Jalan Permatang Pauh and was occupied in August 2003. The first intake of students in UiTM Pulau Pinang implemented in July 1996 with the enrollment of 230 students. The first group of students who graduated from UiTM Pulau Pinang was in May 1999. The staff here is the beginning of a total of 40 people, including nine academic staff. The main focus is to UiTM Pulau Pinang electrical engineering, mechanical and civil diploma. The permanent campus building was planned since 1995 with a capacity of 10,000 enrollments in engineering, hotel management and tourism as key areas.